A research report on the feasibility of community management of ear patients through integration of tele-otology in existing community level health facilities at the periphery of Kathmandu valley. - Mathema, Luna (2021)
SUMMARY: In a developing country like ours where specialized human resources are scarce, geographical terrain is difficult and awareness about ear disease is minimal, tele-otology can fill in the gap. These difficult times of pandemic have opened the virtual world of possibilities. As most of the otological diagnosis is based on objective image finding, studies internationally have shown good results. So, in this study, we will be integrating teleotology in existing community-based health services of CHHERS. We want to see the acceptance of tele-otology/ virtual consultation by our community along want to see the acceptance of tele-otology/virtual consultation by our community along with the feasibility of teleconsultation in real-time. The result of this study will help us to pave the way of similar programs in remote areas but also financially lessen the burden of the community by saving their time & money for travel. And we also believe that this can increase the awareness and timely detection of ear diseases. This cross-sectional descriptive study was carried among the patients visiting outreach centers of Hospital for Children Eye Ent and rehabilitation services, having tele-otology services. Data was collected by trained community ear health workers through face-to-face interview, ear examination using and otoscope and video conferences with ENT surgeons using the zoom platform. The collected data was checked every day to avoid the data collection error and entered into EpiData 3.1 provided with checks to avoid possible data entry error. This was analyzes using the statistical package for social science version 26. Univariate, bivariate and multivariate analyses were done. The findings of this study will be shared with NHRC, MoHP, DoHSand other stakeholders. These study findings will be useful for policymakers and health care managers to provide service during pandemics like COVID-19, and also for planning to provide specialist ear care service through integrating tele-otology service in the existing health center.